Women as the Other Within and Towards Christianity: A Variation of Marianne Moyaert’s ›History of Religionization‹ - Zimmermann, Katharina (Campus der Theologien, 2025)
Based on Marianne Moyaert’s study on the construction of Christian identity, this article examines how, in relation to the category of ›gender‹, the female counterpart was constructed as the other to male Christianity, analogous to the religious counterpart as presented by Moyaert. However, women could not simply be excluded from the Christian community for reproductive reasons. Instead, Christian actors pursued a double strategy: In addition to the othering of women, an illusory point of reference for female existence within Christianity was created through the construction of an ideal of female purity. Methodologically and structurally oriented towards Moyaert’s work, the article uses Jerome, John Meyer and Pius XI. as historical highlights to verify the thesis.